2020
DOI: 10.1111/cmi.13254
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gulae lipopolysaccharide elicits inflammatory responses through toll‐like receptor 2 and 4 in human gingivalis epithelial cells

Abstract: Porphyromonas gulae, a Gram‐negative black‐pigmented anaerobe, has been associated with periodontal disease in companion animals and its virulence has been attributed to various factors, including lipopolysaccharide (LPS), protease and fimbriae. Toll‐like receptors (TLRs) recognise pathogen‐associated molecular patterns, such as peptidoglycan, lipids, lipoproteins, nucleic acid and LPS. Following P. gulae infection, some inflammatory responses are dependent on both TLR2 and TLR4. In addition, a recent clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Moreover, P. gingivalis has been shown to have the ability to invade human host cells, degrade cellular focal adhesion components, and induce apoptosis in a fimA -types-dependent manner [ 16 , 47 , 48 ]. Recent studies have noted that P. gulae organisms express several different virulence factors, including fimbriae, LPS, and trypsin-like proteases [ 3 , 7 , 49 , 50 ]. P. gulae LPS was found to induce inflammatory responses in human gingival epithelial cells, while cell viability was not affected [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, P. gingivalis has been shown to have the ability to invade human host cells, degrade cellular focal adhesion components, and induce apoptosis in a fimA -types-dependent manner [ 16 , 47 , 48 ]. Recent studies have noted that P. gulae organisms express several different virulence factors, including fimbriae, LPS, and trypsin-like proteases [ 3 , 7 , 49 , 50 ]. P. gulae LPS was found to induce inflammatory responses in human gingival epithelial cells, while cell viability was not affected [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have noted that P. gulae organisms express several different virulence factors, including fimbriae, LPS, and trypsin-like proteases [ 3 , 7 , 49 , 50 ]. P. gulae LPS was found to induce inflammatory responses in human gingival epithelial cells, while cell viability was not affected [ 49 ]. On the other hand, P. gulae proteases have been reported to degrade host tissue components related to growth and proliferation, resulting in promotion of morphological changes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Porphyromonas sp. can confer cancer cells with enhanced tumor invasion and metastatic capabilities by promoting matrix metalloproteinase 9 (MMP9), an extracellular matrix degrader, through activation of protease-activated receptor 2 (PAR2) and the ERK1/2-Ets1/3-p38 pathway ( 37 , 38 ) ( Figure 1 ).…”
Section: Is Porphyromonas Gingivalis the Link Betw...mentioning
confidence: 99%
“…On the contrary, Chukkapalli et al [ 34 ] observed that a marked reduction of aortic plaque area and intimal thickness in TLR2 −/− TLR4 −/− -, TLR2 +/− TLR4 −/− -, and TLR2 −/− TLR4 +/− -deficient mice infected with multiple periodontal pathogens compared with normal group. Inaba et al [ 35 ] found that the p38 and ERK1/2 phosphorylation, a potent activator of mitogen-activated protein kinase (MAPK) pathways acted as initiating inflammation, was decreased in TLR2 and TLR4 gene knockdown gingival epithelial cells. These results clearly demonstrated that partial or complete knockdown of gene of TLR2 and TLR4 reduces the progress of atherosclerotic plaque in infected animal models.…”
Section: Links Of Periodontal Infection and Atherosclerotic Cerebrova...mentioning
confidence: 99%
“…TLRs, the most characteristic members of pattern recognition receptors, are widely expressed in the various cell membrane or located in the cytoplasm, and the elevated levels of TLR expression in macrophages and endothelial cells of atheroma have been observed [ 66 ]. Inaba et al [ 35 ] demonstrated that P. gingivalis LPS enhanced the expression of TLR2 and TLR4 mRNA in human gingivalis epithelial cells. In vivo trial performed by Nakamura et al [ 67 ] also suggested that TLR2 might take charge for recognizing the fraction of P. gingivalis LPS and mediating mononuclear cell adhesion to the vascular endothelium.…”
Section: Role Of Tlr Signaling In Periodonpathic Pathogen-induced Ath...mentioning
confidence: 99%